Why are animate dishes so disturbing? - Spence, C (Elsevier, 2018)
Most foods are relatively static on the plate. Food that moves, especially if it does so in an animate manner, captures our attention in a way that would seem to play to society's growing interest with ‘food porn’. At the same time, however, most diners appear to find such movement on the plate or in the bowl rather disconcerting to say the very least. Such animacy may be aversive, ‘horrifying’, in fact, being a term that one sometimes sees used in this context. According to one suggestion, this may be because of a primordial fear of asphyxiation on eating food that still has the capacity to move of its own volition. According to others, however, there may also be something of a taboo around harming living things that many meat eaters try to mitigate by, for example, not calling the animals they eat by the name of the beast: Think steak or beef for cow and pork chop or bacon for pig. It may simply be that it is harder to suppress such thoughts related to the life that was lost, what some call the ‘meat paradox’, when food is animate. The breaking of some sort of taboo might also help to explain the excitement that some feel when they think about eating something that moves. In this article, I provide a brief historical overview of the diner's/chef's/advertiser's fascination with the visual transformation of food on the plate or in food advertising. I take a look at movement, both animate and inanimate, as well as other kinds of transformations, such as foods that change colour before the diner's very eyes. I also look at how technological advances are increasingly starting to offer the creative chef/food designer the opportunity to bring food to life in a way that doesn’t necessarily trigger any concerns with animal welfare, nor threaten the diner with asphyxiation.